Promoting supportive and palliative care research by a management fellow. (1st April 2011) - Donaldson, A; Barclay, S; Dale, J; Daveson, B; Epiphaniou, E; Harding, R; Higginson, I J; Mason, B L; Munday, D; Nanton, V; Shipman, C; Murray, S A
Abstract : Abstract: Introduction and aims: Following a successful bid to undertake research into co-ordination of palliative care needs of patients within the generalist setting, the research team was offered the opportunity to employ an NHS manager to become a 'Management Fellow.' The aim was to provide a means to embed research expertise in the local NHS area through the personal development of the fellow: including training in research methods, assistance in all stages of the research process and taking a lead in the subsequent dissemination throughout the clinical areas. Method: We enlisted a Clinical Nurse Manager half time while she continued to work 50% within the Acute Hospital structure. The management fellow recruited has become immersed in the world of research. The fellow is also the subject of an auto-ethnographic exploration of the tensions involved in integrating her own clinical practice with her role as a researcher. Results: Initial findings show that the management fellow has adapted to the joint clinical management/research role, facilitating integration into research site, assisting with recruitment of participants and identifying methods to ensure effective knowledge exchange and mobilisation within her substantive role as Clinical Nurse Manager. Conclusions: Early indications are that by ensuring a management representative on the research team the research pathway can be smoothed to allow effective research to be undertaken. The management fellow is ideally place d to facilitate the research team's presence and through immersion becomes supportive and understanding of the importance of research. Finally the management fellow is well situated to ensure effective knowledge mobilisation within the clinical areas.